The best lawyer in a one-lawyer town : a memoir - Bumpers, Dale. (Fayetteville : University of Arkansas Press, 2004)
If Frank McCourt had grown up in Depression-era Arkansas, he might write like Dale Bumpers, one of the most colorful, entertaining, and wise politicians in recent American history, Atticus Finch with a sense of humor. In The Best Lawyer in a One-Lawyer Town, Bumpers tells the story of his remarkable journey from poverty to political legend, and the result is a great American memoir that has attracted wide acclaim for its clever southern charm.
JSTOR
Keywords: Bumpers, Dale; United States. -- Congress. -- Senate -- Biography; Bumpers, Dale; États-Unis. -- Congress. -- Senate -- Biographies; Bumpers, Dale; United States. -- Congress. -- Senate; Legislators -- United States -- Biography; Governors -- Arkansas -- Biography; Lawyers -- Arkansas -- Biography; Arkansas -- Politics and government -- 1951-; Parlementaires -- États-Unis -- Biographies; Gouverneurs -- Arkansas -- Biographies; Arkansas -- Politique et gouvernement -- 1951-; Lawyers & Judges; Governors; Lawyers; Legislators; Politics and government; Arkansas; United States; Since 1951; Biographies